2016
DOI: 10.1002/mar.20918
|View full text |Cite
|
Sign up to set email alerts
|

Hippies, Greenies, and Tree Huggers: How the “Warmth” Stereotype Hinders the Adoption of Responsible Brands

Abstract: Past research has highlighted the difficulty faced by responsible consumers, individuals who wish to make environmentally and socially responsible consumption choices. Individual buyers, it is argued, act within a network of structural and social relationships that make responsible alternatives intrinsically hard to pursue. This paper maintains that one such barrier is the perception that users of responsible brands are not worthy of social emulation. Consumers are less likely to adopt brands positioned explic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 87 publications
(203 reference statements)
0
49
0
1
Order By: Relevance
“…Another suggested barrier to choosing sustainable products is that goods are core to consumer identity (Antonetti and Maklan ); this is especially important when their role as a differentiator is appealing (Belk ), which is the case in the context of luxury. Significant psychological benefits stem from purchasing and owning luxury products: consumers are seeking to create a personal brand identity, feel good about themselves (self‐identity), or impress others (peer identity) (Davies et al .…”
Section: Research Streamsmentioning
confidence: 99%
“…Another suggested barrier to choosing sustainable products is that goods are core to consumer identity (Antonetti and Maklan ); this is especially important when their role as a differentiator is appealing (Belk ), which is the case in the context of luxury. Significant psychological benefits stem from purchasing and owning luxury products: consumers are seeking to create a personal brand identity, feel good about themselves (self‐identity), or impress others (peer identity) (Davies et al .…”
Section: Research Streamsmentioning
confidence: 99%
“…For example, Graham‐Rowe et al () found that consumers labeled electrical vehicle users as dull or tree‐huggers. Social stereotyping (e.g., derogatory nicknames) associated with SR consumers represent mental impediments to adopting sustainable alternatives (Antonetti & Maklan, ). The attitude‐behavior gap (Schlaile et al, ) suggests consumers claim to be responsible, but their actions appear to be incongruent with their beliefs (d'Astous & Legendre, ; Yeow, Dean, & Tucker, )—thus, supporting the need for further research into the SRCB of millennial consumers.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Studies have found that despite the presence of SR and proenvironmental attitudes among millennials, these attitudes do not always translate into actual behavior (Gaudelli, 2009); hence, it becomes critical to ensure that the behaviors measured reflect the actual SR behaviors of millennials. Research has also discussed motivations and barriers to adopting ethical and SR behavior (e.g., Antonetti & Maklan, 2016;Burgess, King, Harris, & Lewis, 2013;Carrington, Neville, & Whitwell, 2010). Consumers resist adoption of more sustainable options (i.e., electric cars) due to negative stereotypes associated with sustainable options (Burgess et al, 2013).…”
Section: Millennials and Social Responsibilitymentioning
confidence: 99%
“…Research generally emphasizes the triggers of sustainable consumption behavior in the traditional economy (McDonagh, P., & Prothero, 2014). Sustainable consumption behavior includes various forms, such as energy-saving behavior (Wang et al, 2011), food consumption (Sahakian, Marlyne, Wilhite, 2014), green product purchase (Antonetti, P., 2016) and product disposal (Mccollough, 2010).…”
Section: The Concepts and Principles Of Sharing Economymentioning
confidence: 99%